Nutritional Status Assessment in ICU Patients Using Ultrasound Imaging of Muscles and Subcutaneous Fat - R. E. Lakhin; M. V. Nikitin; E. Yu. Strukov; A. A. Emelyanov; A. G. Klimov; B. N. Bogomolov; A. I. Levshankov; A. V. Schegolev (Общая реаниматология, 2020)
Ultrasound imaging of muscles and subcutaneous fat has been used in recent years to assess the nutritional status, but there are no common approaches for selecting muscles for it.The aim of the study was to examine the variability of thickness of different muscles and subcutaneous fat using ultrasonography to identify optimal cutaneous and muscle landmarks for the assessment of nutritional status.Materials and methods. It was a prospective observational study with participation of 14 patients. All patients underwent ultrasound examination of thickness of the following muscles: m. rectus femoris; m. tibialis anterior; m. biceps brachii; m. deltoideus and m. sternocleidomastoideus, as well as the thickness of skin and subcutaneous fat over the muscles. The ultrasound assessment was done on admission to ICU, on days 7, 14, 21, 28, 42. On days 7, 14 and 21 the intravenous load test of 1000 ml of 0.9% sodium chloride solution was performed. On days 5 and 10 the test with the patients in the lateral decubitus position was carried out.Results. We found that m. tibialis anterior changed its size when patients were turned laterally by 2%, m. deltoideus by 6%, m. sternocleidomastoideus by 10%, m. rectus femoris by 20.5%, and m. biceps brachii by 26%. After infusion of 1,000 ml of 0,9% sodium chloride solution, the variability of m. tibialis anterior size was 2%, m. deltoideus 2%, m. sternocleidomastoideus 6%, m. biceps brachii 8%, m. rectus femoris 12%.The thickness of subcutaneous fat over m. biceps brachii and m. rectus femoris changed more than the anteroposterior size of the muscles (P<0.05).Conclusion. The m. deltoideus and m. tibialis anterior are optimal for ultrasound assessment of the nutritional status because their size is less affected by the patient's positioning and infusion therapy. Intravenous fluid infusion increases the variability of subcutaneous fat thickness.